A review on fluid structure interaction in hydraulic turbines: A focus on hydrodynamic damping. (July 2017) - Trivedi, Chirag
Abstract: Hydraulic turbines include stationary and rotating components. The interaction of the components, mainly between the runner blades and distributor vanes, is critical when the frequency of the rotor-stator interaction (RSI) approaches the runner natural frequency. This causes resonance in the turbine runner and the premature failure of the blades. Several turbines have experienced such problems in the last few years. The studies indicated that the added mass effect causes change in natural frequency of the runner. In the critical conditions, when the runner natural frequency is close to the RSI frequency, hydrodynamic damping is an important parameter in controlling turbomachinery blade-forced response. A reliable technique that can predict/estimate the change in the runner natural frequency due to added mass has yet to be developed. This paper reviews the investigations conducted on fluid structure interaction (FSI) focusing on the role of hydrodynamic damping during resonance, RSI and added mass effect. In specific, the review includes: (1) role of boundary layer to improve the damping effect, (2) how nearby structure and submergence level changes the damping effect, (3) dependency on mode-shape, (4) how freestream velocity and vortex shedding helps to increase damping, (5) damping during cavitation, (6) damping variation with respect to a dimensionless β parameter and (7) damping effect during rotation. In the summary, need for the future study of FSI within the field of hydropower and how damping is important in avoiding the catastrophic failures in the early life of hydraulic turbines is discussed. Highlight: Hydrodynamic damping is dependent on nodal-diameter of the mode shape. The damping effect is proportional to the freestream flow velocity. Damping is significant when a structure subjects to out-of-phase deformation. Damping is more when boundary layer flow creates full-Rankine oval. Gap in the labyrinth seals plays critical role in structural damping at resonance.